Complex effects of acid rain and cadmium on growth and antioxidase system of alfalfa - XU Su-ling; FANG Yong; XING Cheng-hua (浙江大学学报. 农业与生命科学版)
A pot experiment was conducted to study complex effects of simulated acid rain and Cd on the growth and physiological characteristics of alfalfa. The results indicate that dry matter contents of root and aerial part, contents of total chlorophyll, chlorophyll a and chlorophyll b were higher than those of no Cd treatment under the same simulated acid rain treatment with 5 mg·kg-1 Cd splashing; when Cd concentration increased further, the growth of alfalfa was inhibited, superoxide dismutase (SOD) activity decreased significantly, and the changing tendency of malondialdehyde (MDA) content was opposite to SOD activity. Peroxidase (POD) activity firstly increased gradually to achieve the maximum and then decreased along with Cd concentration increasing, but catalase (CAT) activity always increased as Cd concentration increased. Under the stress of acid rain at pH 3.5, alfalfa was harmed most seriously. Simulated acid rain and Cd complex pollution had significant interactive effects on the dry weight of aerial part, content of MDA, activities of SOD and POD in the alfalfa.